A meta indução otimista : uma explicação realista para o progresso científico - Lustosa, Eduardo Moreira (2021)
This work is a defense of the optimistic meta induction, that is, the belief that scientific theories tend to get better over time. It is also a defense of scientific realism, i.e., the theory that the best scientific theories of today are approximately true in their descriptions and explanations of the world. So, from the beginning, the cards are on the table. Throughout the dissertation, we will try to justify our adoption to the theories of optimistic meta induction and scientific realism by the studies of the best scholars of the matter and with practical examples from current science and from the history of science. The study of the paradigmatic case of the theory of black holes will be especially enlightening, since its emergence, unfolding from the General Theory of Relativity, almost as a mere mathematical eccentricity, until its empirical confirmation, through photography, more than one hundred years later. In the sequence, in perhaps the most original part of our study, we will demonstrate that science and technology were once fields that were not very communicating to each other, but since the 20th century, the interaction has been constant, bringing progress to both areas. In the end, consistent with our realistic conception of science, we will defend that even (still) unobservable entities - namely, objects that cannot be observed by current technology - described by the best present theories are real and their explanations are approximately true.